Performance Management System And Accountability Commitments: A Case Of A Malaysian Ngo - Ibrahim, Suraiya (2019)
The role of the performance management system (PMS) in non-governmental organisations (NGOs) has been argued to be both complex and challenging. Despite considerable research conducted on NGOs, the intent readings on PMS issues surrounding NGOs are currently very limited. Instead, previous research about NGOs had given much focus on the mere structural content of the organisations and their responsibilities to advance particular interests within their specific contexts. Given the limited literature on PMS, the current research was undertaken to examine one NGO, in terms of the ways it manages its performance to meet various institutional expectations. To be more specific, the research has been conducted to understand and analyse the role of PMS in meeting the lines of accountability (commitments) towards various stakeholders that the NGO wishes to serve. To achieve these goals, an in-depth study has been employed in this research by utilising the qualitative research approach. Inspired by Ferreira & Otley’s (2009), PMS framework and New Institutional Sociology (NIS), this study explained how PMS is affected by the process of discharging the accountability commitments of the studied NGO. This study had established that the emerging normative isomorphic forces acquired from the PMS, and the accountability practices had dominated the NGO’s setting over coercive forces. Interestingly, mimetic isomorphism appeared to be limitedly enforced in this NGO.